Retreatment of men with metastatic castrate‐resistant prostate cancer with abiraterone. Issue 14 (11th August 2014) - Leibowitz‐Amit, Raya; Alimohamed, Nimira; Vera‐Badillo, Francisco E.; Seah, Jo‐An; Templeton, Arnoud J.; Knox, Jennifer J.; Tannock, Ian F.; Sridhar, Srikala S.; Joshua, Anthony M.
Abstract BACKGROUND Abiraterone acetate (AA), oral CYP17 inhibitor, is an active agent in the treatment of metastatic castrate‐resistant prostate cancer (mCRPC). METHODS We (R.L.A and N.A) retrospectively evaluated outcome in 12 men who were re‐treated with AA following prior treatment with AA at the Princess Margaret Cancer Centre. RESULTS All men were heavily pre‐treated for mCRPC with a median of four prior lines of therapy, one of which was AA (given either pre‐ or post‐chemotherapy). Eleven out of 12 (92%) men stopped their first treatment course of AA due to progression and one stopped for financial reasons. Seven men had a PSA decrease ≥50% following their first AA treatment, of which three (46%) had a PSA decrease ≥50% to AA re‐treatment. The responses to AA re‐treatment were generally short‐lived with a median biochemical progression‐free survival of 2.3 months and median treatment duration of 3.2 months. No PSA responses to AA re‐treatment were seen in five men who did not have an initial PSA response to AA. CONCLUSIONS Our data suggest that AA re‐challenge may have limited benefit in select men with mCRPC, and warrants further formal research. Prostate 74:1462–1464, 2014. © 2014 Wiley Periodicals, Inc.